Analysis of Fungal Diversity, Physicochemical Properties and Volatile Organic Compounds of Strong-Flavor Daqu from Seven Different Areas - Zhigao Li; Xu Yan; Sibo Zou; Chaofan Ji; Liang Dong; Sufang Zhang; Huipeng Liang; Xinping Lin (Foods, 2024)
Strong-flavor Daqu, as a fermentation agent, plays a significant role in shaping the quality of strong-flavor baijius, and fungal species in Daqu are important factors affecting the quality of Daqu. Therefore, we selected strong-flavor Daqu from seven different origins to study the fungal composition and the effects of the fungal composition on the physicochemical properties and volatile organic compounds (VOCs). It was found that the fungal composition influences the physicochemical properties of Daqu. Specifically, there was a positive link between Rhizomucor, Rhizopus, Thermomyces, and liquefying activity and a positive correlation between Aspergillus and fermenting activity. Furthermore, the relationships between esterifying activity and Thermomyces, Rhizomucor, Aspergillus, Pichia, and Saccharomycopsis were found to be positive. The VOCs in Daqu were affected by Aspergillus, Issatchenkia, Pichia, and Thermoascus. Issatchenkia was significantly positively correlated with benzeneethanol as well as Aspergillus and pentadecanoic acid ethyl ester, ethyl myristate. Pichia and Thermoascus were significantly negatively correlated with benzaldehyde and 2-furaldehyde. This study deepens our understanding of the relationship between VOCs, the physicochemical properties with microbial communities, and reference significance for the production of better-quality strong-flavor Daqu.